The composition of bee pollen color fractions evaluated by solid-state 1H and 13C NMR: their macroelement content and antioxidant properties. Issue 5 (20th October 2017) - Paradowska, Katarzyna; Zielińska, Agnieszka; Kuras, Marzena; Wawer, Iwona
Abstract : Honey bee pollen is a good source of nourishing substances with a wide range of potential therapeutic properties. The aim of the present study was to evaluate the composition and antioxidant activities of bee pollens collected from commercial hives in Poland. Plant sources were buckwheat and rapeseed. The pollen loads differed in color, so samples were separated into color fractions. The highest content of minerals (K, Ca, P) was in samples from: buckwheat (S1) and rapeseed (S7). The rapeseed pollen had significantly higher amounts of polyphenols and flavonoids, and higher values of antioxidant capacities as measured by DPPH, FRAP and ORAC assays. 13 C CPMAS NMR spectra revealed the presence of carbohydrates (including polymers), lipids, polyphenols and amino acids. Solid-state 1 H MAS spectra showed the resonances of lipids, sugars and different amounts of water. Our results indicate that 1 H and 13 C MAS NMR spectroscopy can be very useful to characterize bee pollen types.